Productive Waqf Empowerment Through the Community Development Program : Case Study at Madina Dompet Dhuafa Zone in the Parung Region, Bogor Regency - Agustin Windia; Rivia Hisanah (Iqtishodia: Jurnal Ekonomi Syariah, 2021)
Waqf is one of the instruments in Islamic economics that aims to achieve goals in Islamic economics, namely realizing a prosperous community life. An integrated productive waqf empowerment program has been implemented by the Dompet Dhuafa waqf institution through the Community Development program in the Madina Zone.This study aims to determine the stages of community empowerment in the Madina Zone which are assessed for effectiveness in terms of business unit growth and to determine the implementation of economic empowerment programs in the Madina Zone area. This type of research is a type of descriptive qualitative research. The results of this study conclude that measurement and analysis of several business units under study, namely Rumah Kemasan, Ornamental Fish Cultivation and Dayamart retail. During this pandemic, those types of businesses studied have significant decrease in turnover and activity. This study also sees the need for waqf managers (nazhir) who not only understand waqf and waqf governance but also explore the managerial aspects of the type of business that is fostered and assisted.